2010
DOI: 10.1177/0363546509359072
|View full text |Cite
|
Sign up to set email alerts
|

Single- Versus Double-Bundle Posterior Cruciate Ligament Reconstruction

Abstract: The need for a posteromedial graft during posterior cruciate ligament reconstruction is questioned, especially in view of the relatively high graft forces at full extension that could cause it to permanently elongate with time. If a double-bundle reconstruction is performed, there is no biomechanical advantage in making the bone bridge between tunnels less than 3 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 8 publications
2
50
1
Order By: Relevance
“…7 Biomechanical studies have shown that the key determinant in controlling posterior tibial laxity in anatomic PCLR is the femoral tunnel placement on the medial wall and roof of the intercondylar notch. 18 Consequently, a trifurcate graft is the construct of choice for surgeons performing both open 19 and arthroscopic tibial inlay 9,20 PCLR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Biomechanical studies have shown that the key determinant in controlling posterior tibial laxity in anatomic PCLR is the femoral tunnel placement on the medial wall and roof of the intercondylar notch. 18 Consequently, a trifurcate graft is the construct of choice for surgeons performing both open 19 and arthroscopic tibial inlay 9,20 PCLR.…”
Section: Discussionmentioning
confidence: 99%
“…These measurements are similar to those recommended by LaPrade and colleagues 7 and other authors. 5,8,9 The femoral sockets are also created through the AM portal with the retrograde drill. For GraftLink constructs, a 20-mm socket is created in the AL position, and for TriLink, an additional 20-mm socket is created at a different angle to accommodate the PM bundle.…”
Section: Femoral Socket Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…5,16,18 A proliferation of biomechanical studies were undertaken to delineate the exact form that a two-bundle procedure should take. 6,11,14,19,20 Some surgeons focused on eliminating the ''killer turn'' at the entrance to the tibial tunnel and became avid fans of the inlay technique. 3,8,23 We all know what happened in recent years.…”
mentioning
confidence: 99%
“…Not all cadaveric studies have demonstrated an advantage of double-bundle reconstruction, 2,3,6,23 and some have raised concerns that this technique might abnormally constrain the knee. 14,24 Although these two new comparative studies will help inform the debate on the merits of double-bundle PCL reconstruction, the number of bundles is just one variable that can influence the outcome of this surgery. When a PCL reconstruction is undertaken, the surgeon must not only choose the number and spacing of bundles but also the graft material, fixation method, femoral tunnel position, 4,12,19,20,22 tibial inlay versus tunnel approach, 15 tensioning position and technique, 4,11 reconstruction method for the PLC or other associated injuries, 13,21,24 and details of postoperative mobilization and rehabilitation.…”
mentioning
confidence: 99%